Hazardous waste handbook for health and safety - Martin, William F.; Lippitt, John M.; Webb, Paul J. (Paul Joel), 1962- (Boston : Butterworth-Heinemann, 2000)
Hazardous Waste Handbook 3E offers a straightforward approach to protecting workers who clean up the nation's hazardous waste sites and chemical spills. Supervisors and site inspectors will find this handbook very useful in answering occupational health questions at the work site. The manual covers such topics as site characterization, air monitoring, personal protective equipment, decontamination, and site emergencies. Numerous health and safety checklists, hazardous-chemical data sheets, and personal protective equipment recommendations are presented for field decisions. The goal of the book is to provide practical information on protecting workers while also containing the high cost of hazardous chemical waste cleanups. Provides practical information on protecting workers and keeping cleanup costs down Designed to allow supervisors and site inspectors to find information quickly Offers numerous health and safety checklists, hazardous chemical data sheets, and recommendations on protective equipment.
Laws and regulations -- Hazards -- Planning and organization -- Site characterization -- Air monitoring -- Personal protective equipment -- Site control and work practices -- Decontamination -- Spills and site emergencies -- Medical monitoring programs -- Training -- Monitoring well safety at hazardous sites -- Hazardous waste transportation safety.
Includes bibliographical references and index.
Keywords: Hazardous waste sites -- Safety measures -- Handbooks, manuals, etc; Hazardous waste sites -- Health aspects -- Handbooks, manuals, etc; Environmental health -- Handbooks, manuals, etc; Hazardous Waste -- Handbooks; Environmental Monitoring -- Handbooks; Environmental Pollution -- Handbooks; Occupational Health -- Handbooks; Safety Management -- Handbooks; Electronic books; Handbooks, manuals, etc